Effects of marine seismic surveys on free-ranging fauna: a systematic literature review - Affatati, Alice; Camerlenghi, Angelo (Frontiers in Marine Science, 2023)
Among anthropogenic activities, marine seismic surveys are a fundamental tool for oil and gas explorations, geophysical research, environmental hazard, and risk analysis. This resulting noise may affect a range of species, eliciting masking, behavioral responses, and changes in acoustic repertoires. There is an urgency to understand in depth the potential effects of seismic surveys on marine ecosystems since the information available is still scarce. Using Scopus® and Web of Science™ 2023 Clarivate bibliographic databases, we systematically reviewed the scientific literature addressing seismic surveys’ effects on free-ranging marine fauna. The first selection of articles matching selected keywords yielded 680 articles from Scopus and 320 from Web of Science. Screening for research articles written in English investigating marine fauna in its natural environment and performing a quality assessment process resulted in selecting 31 articles since 2001. We found a trend of increasing research efforts in this field with a decrease after 2020 and a broad spectrum of journals that hosted the publications (31 papers published in 12 journals). Although several taxa are investigated, most studies focused on effects on marine mammals. There is a lack of research on diverse animal taxa, and no research papers compare the effects on different taxa along the food chain. Behavioral and physiological effects are the most found by authors in the field. However, observed behavioral changes cannot always be uniquely attributed to the exposure to seismic surveys, as many authors report the influence of other variables (e.g., environmental conditions) during the observations.